Pregnancy Induced Porphyria Cutanea Tarda - Shanker B; Mohan K; Sentamilselvi G; Janaki V; Pandurangan C.N (Wolters Kluwer Medknow Publications, 2000)
Prophyria cutanea tarda induced by pregnancy in a 20 year old primi is described along with clinical, biochemical and histological features. All the lesions expect hypertrichosis resolved following childbirth.